2011
DOI: 10.3102/0034654310378174
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Computer-Assisted Instruction in Statistics

Abstract: Although previous meta-analyses have documented the efficacy of computerassisted statistics instruction, the current study examined a range of specific features that presumably influence its effectiveness, such as the level of learner engagement, learner control, and the nature of feedback. In 45 experimental studies with a control condition, computer-assisted statistics instruction provided a meaningful average performance advantage (d = 0.33). Because of great methodological heterogeneity among the studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 73 publications
3
44
1
4
Order By: Relevance
“…The findings of the studies indicated that CALL-laden approaches proved beneficial for language and pronunciation teaching and these sorts of activities enhanced students' skill and performance to a greater degree. Interactive technology can enable students to organize information so that it can be connected to their prior knowledge or existing schemata (Sosa, Berger, & Mary, 2011). Lambacher (1999) used pronunciation software to forty primary school Japanese learners.…”
Section: Empirical Researches On Call/capt Softwarementioning
confidence: 99%
“…The findings of the studies indicated that CALL-laden approaches proved beneficial for language and pronunciation teaching and these sorts of activities enhanced students' skill and performance to a greater degree. Interactive technology can enable students to organize information so that it can be connected to their prior knowledge or existing schemata (Sosa, Berger, & Mary, 2011). Lambacher (1999) used pronunciation software to forty primary school Japanese learners.…”
Section: Empirical Researches On Call/capt Softwarementioning
confidence: 99%
“…Simulating and experimenting with data in an interactive manner is thought to be a more effective way to assimilate and understand complex and abstract concepts than using traditional methods in the classroom (Sosa, Berger, Saw, & Mary, 2011;Gonzaĺez, Jover, Cobo, & Munõz, 2010;Dinov, Christou, & Sanchez, 2008;Lunsford, Rowell, & Goodson-Espy, 2006). It is expected that these interactive electronic resources do the calculations in the background and show the visual results interactively, thus allowing students to focus on exploring and investigating simulated or real-life examples (Bolliger, & Supanakorn, 2011;Chance, Ben-Zvi, Garfield, & Medina, 2007), as well as in geovisualisation (Sigala, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been many attempts to overcome this problem in statistics education generally using interactive learning tools. It has been widely recognized that the effectiveness of the learning process is enhanced by means of experimenting and simulating, usually with digital tools [1], [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%